Effect of N-acetylcysteine supplementation on oxidative stress-mediated cryoinjury of bone marrow derived-hematopoietic stem cells - Shawal Maradona Abdul Wahab; Zariyantey Abd Hamid; Ramya Dewi Mathialagan; Izatus Shima Taib (Penerbit Universiti Kebangsaan Malaysia, 2019)
Hematopoietic stem cells (HSCs) transplantation was introduced as curative treatment for various diseases. Cryopreservation of HSCs is crucial for long term storage and maintenance of cellular quality; however, it has been reported that cryopreservation itself causes oxidative stress-driven apoptosis and cell loss. This study investigated impact of supplementing N-acetylcysteine (NAC) as antioxidant during cryopreservation on viability and oxidative stress in HSCs. HSCs were isolated from murine bone marrow, cultured in HSCs growth media and cryopreserved (1×106 cells per vial) together with 10% DMSO and NAC (0, 0.25, 0.5 or 2.0 μM) for 48 h, 2 weeks or 8 weeks at -196°C using controlled-rate-freezing technique. Cell viability and oxidative stress in cryopreserved cells were analysed at each time-point. Cell viability was significantly reduced (p<0.05) following cryopreservation as compared to pre-cryopreservation. NAC supplementation significantly increased cell viability (p<0.05) after 48 h cryopreservation at 0.5 μM and 2.0 μM and after 2 weeks cryopreservation at 0.25 μM compared to the controls. Cryopreservation significantly enhanced GSH level (p<0.05) and reduced MDA level (p<0.05) without affecting SOD activity and PC level in HSCs compared to pre-cryopreservation. NAC supplementation significantly increased GSH level at 0.25 μM in cryopreserved HSCs compared to control. In conclusion, NAC supplementation during cryopreservation showed potential in minimizing cryoinjury by promoting cell viability, increasing antioxidant capacity and reducing oxidative damage in HSCs, however these effects are influenced by both durations of cryopreservation and NAC concentration.